PENGARUH MANAJEMEN KELAS DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA DI MTS AT TAUFIQ BOGEM - Sulis, Sulis Fitria Ningrum; Suwandi (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to determine the influence of classroom management and the school environment on student learning motivation. This research uses a quantitative approach with an ex post facto type of research. The sample in the research was 84 students as respondents, and used non-probability sampling with a saturated sampling technique. Data collection was carried out using a questionnaire with 30 statement items. And using multiple linear regression test data analysis techniques. The results in this study show that. (1) there is a partial influence between class management on student learning motivation with a significance value of 0.026 < 005 and a result of T= 2.260 > 1.993. (2) there is a partial influence between the school environment on student learning motivation with a significance value of 0.000 < 0.05 and a result of T= 6.178 > 1.993. (3) there is a simultaneous influence between classroom management and the school environment on student learning motivation with a significance value of 0.000 < 0.05 and results F= 19.420 > 2.72.